The impact of Daniel's model on acquiring historical concepts among second-grade students and developing their motivation towards learning (Journal of the College of Basic Education, 2022)
The present study aims at identifying The Danial Strategy in acquiring the historical Concepts at the second intermediate pupils and devcloping their motives towards learning. The folloning nnu hypotheses are written: -There is no significant difference at the level of O.O5 between the mean scores of the experimental group who were taught Daniel Stralegy and the control group which was tanght by the classical methuo. There is no signifant difference at the level of O.O5 between the mean scores of the experimental group and the control group in the scale of motivation. There is no significant difference at the level of O.O5 a is the mcan scores of the experimental group due to Daniel Strategy in the scale of Mativation ot the pre-post test.The study is limited to: - The malepupils of the 2nd intermediate schools (day) at Al-Rusafa First- Directorate general (2016-2017). - The third, fonrth and the fifth chapters taken from History book for the Academic year (2016-2017)The second semester (2016-2017( The experimental design was the partial – control design was chosen. The testing. Acquiring conceptions were the tools of the study. Al-Magrib intermediate school was selected due to the place and the distance to the researcher. The school was very cooperative. It was at the Al-Rusafa1. Two sections were chosen randomly. For the two groups. The sample consists of (50) pupils. (29) for the experimental and (31) for the control group. After excluding the repeaters who were (10) pupile (4) for the experimental and (6) for the control. Both groups were equated by (Age in months) marks in History subject for the first conrse intelligence, and motiration scale. The researcher designed the bavariourial objectives which were (138) and gave them to the Jury who decided their validity. (22) lesson plans were also designed and designed a test for the historical conceptions which contained (60) items and has adopted a scale (Al-Janby 2015) of mcitive scale, ther it was verified and validated then: hac done the relabitity. Spss statis tical bag was used to get the data At was concluded that.- signi fi cant differences at the level of O.O5 in the mean scores of the pupils scores which taught daniels, strategy and the control group which taught the prescribed method and in favour of the experimcntal group. -signi ficaht differnces at the level O.O5 in the mean scores of the experimental and the control group in the scale of motivation and on belzalf of the experimental group.In the light of the results of the reseach. It was recommended that -Using Daniels strategy in the Intermediate -Using Danial Strategy as a supporting techniques and as a supplementary tool.